PELAKSANAAN PROGRAMPENDIDIKAN KECAKAPAN HIDUP (PKH) MENJAHIT BAGI PEREMPUAN DALAM MENINGKATKAN KEMANDIRIAN PESERTA DIDIK di LKP MODES MURIA SIDOARJO - JAWA TIMUR - WIWIN YULIANINGSIH (JPUS: Jurnal Pendidikan Untuk Semua, 2018)
Life skill education is a kind of non formal education program that centered on vocational skill for student, such as sewing skill in a course and training. The purpose of this research is to describe the implementation and result of sewing educational program (life skill education) for women, in order to increase the independence of students. This research is using qualitative method, to collecting the data is using observation, interview, and documentation, to analyze the data  is using data collection, data reduction, data display and verification. While in validity test of data research is using credibility, dependability, confirmability and transferability. This researchs result shows that the implementation in life skill education of sewing can be implemented well, effective and eficient, which we can see from the step by step completion in every component of life skill education organizers, such as; 1) opportunities analyzis, 2) job courses and training, 3) learning result assesment or competence test, 4) placement guarantee when they graduate, so it can produce skilled students and ready to be placed in enterpreneurship and industry. Besides, the increasing of students independence can be seen from several indicators, such as : having creative ideas, dicipline, not depend on other people and able to fulfill daily needs.